Impact of XBRL Technology Implementation on Information Asymmetry in Indonesia’s Capital Market - Wahyudi, Aldika; Anggraini, Dyah (Ikatan Ahli Informatika Indonesia (IAII), 2025)
This research aims to examine whether the publication of financial statements in XBRL format could reduce the level of information asymmetry, measured by the bid-ask spread, in Indonesia’s capital market over eight years of its implementation. Furthermore, this research examines differences in the level of information asymmetry in two observation periods, which are the early stage and the advanced stage of the XBRL implementation. The population in this study are listed companies on the IDX80 index which were sampled using the purposive method. The analytical instrument used is a panel data regression test using a random effect model and the non-parametric Wilcoxon test of statistical differences. Consistent with similar studies, the results show that the publication of financial reports in XBRL format could reduce the level of information asymmetry by providing accurate, integrated, and universally accessible reporting. The difference test further reveals that the level of information asymmetry is lower in the advanced stages compared to the early stages. This suggest that XBRL implementation becomes more effective over time due to the positive developments in institutional readiness and stakeholder facilitation.